Heat Loss Analysis On The Wall Of Coconut Shell Carbonization Tool Into Briquettes - Suwangi, Dayu; Sabani, Rahmat; Murad, (J-AGENT (Journal of Agricultural Engineering and Technology), 2023)
The carbonization process is the process of converting the original raw material into carbon through combustion in a closed space with limited air. The purpose of this study was to determine the amount of heat loss on the walls of the isolated coconut shell carbonization apparatus. The research method used is experimental with field experiments. The carbonization process uses a carbonization drum that has been coated with an insulator in the form of clay on the tool wall. The carbonization process was carried out at temperatures above 100oC for 90 minutes with a weight of 6 kilograms of coconut shell material. In the carbonization process, temperature and pressure measurements were carried out on 3 parts of the wall with a total of 13 measuring points. The parameters calculated in this study are the cross-sectional area of the tool, the value of the tool's conductivity, the heat loss on the wall, and the heat source. Based on the results of carbonization, it was found that the carbonization drum has a cross-sectional area of 1.32m2 with a conductivity value of iron 73 W/moC and clay 2.30 W/moC. The highest heat loss occurred at the upper tool wall, which was 9,893.56 W, while the lowest heat loss occurred at the lower tool wall. that is equal to 8,468,66 W. The average heat loss on the appliance cover is 268,555,63 W. The overall heat loss coefficient for the appliance is 14,665.823 J/m2oC.